ICE BREAKING METHODS TO REDUCE INITIAL TENSION AMONG OFFICER STUDENTS OF THE INDONESIAN NATIONAL ARMED FORCES - Annida Haerunnisa; Adi Heryadi (International Journal of Cultural and Social Science, 2026)
Military cadets who are about to begin their education experience tension caused by the hierarchy and seniority that still exists, adaptation to a new environment, and the cognitive burden of academic tasks that they will face in the coming months. This study aims to eliminate the initial tension experienced by cadets. The method used in this study is descriptive qualitative research, and the data collection techniques used are semi-structured interviews, observation, and literature study. The results of the study show that ice breaking methods are effective in reducing initial tension. The use of ice breaking can reduce tension, creating a more relaxed atmosphere. By conducting ice breaking activities, there was a noticeable change in group dynamics, with cadets feeling much more relaxed, comfortable with other participants, communicating spontaneously, and experiencing reduced tension. Ice breaking plays an important role in creating a pleasant and motivating atmosphere during training.